Solid Biofuel dari Campuran Tongkol Jagung dan Tempurung Kelapa dengan Metode Hydrothermalsebagai Substituen Energi dalam Upaya Reduksi Sampah Pertanian - C. Chika Oktalia Putri; Britania Dewi Clarasinta; Ahmad Tawfiequrrahman (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2017)
Hydrothermal treatment is a thermochemical process that using subcritical water for converting biomass to produce high calorific biofuel. In this method, water actsas reactant, as well as medium of reaction. Experiments was conducted in temperature range of 200-270°C, holding time of 20-40 minutes, biomasswater ratio from 1:7.5 to 1:15 at various composition of coconut shell-corn cob. Based on experimental results, it was found that higher calorific value biofuels produced from treatments with higher temperature since more biomass was decomposed into more carbonaceous products. In addition, longer holding time also raised calorific value due to more complete decomposition. It was also indicated that increasing amount of biomass of the feed raised the calorific value of product. The highest calorific value of product of 5,12 kcal/kg was obtained from the treatment of 270°C, holding time of 30 minutes, biomass-water ratio of 1:10 at the coconut shell-corn cob ratio of 1:1